Implementation of a Low-Volume Power-Type Day to Improve Resistance Training Performance and Recovery - Sousa, Colby (Auckland University of Technology, 2024)
Training recovery is multifaceted. Within this thesis, it describes inter-session resistance training (RT) performance restoration. To enhance performance, sufficient stress often resulting in fatigue occurs. To maximise performance, stress, fatigue, and recovery must be balanced. Despite abundant literature on this topic, findings are equivocal. Therefore, this thesis explored how microcycle (one RT week) configuration affects physiological, perceptual, and performance recovery. First, a literature review examined the influence of RT microcyle configuration on inter-session recovery. Overall, training to failure lengthens recovery and high-volumes may require longer recovery suggesting its cautious use. Training frequency can serve to distribute volume, facilitating fatigue management by providing time for inter-session recovery. Exercises involving lower body, multi-joint, larger muscle groups, longer muscle lengths or eccentric phases may require longer recovery. Daily undulating programming (DUP) structures incorporating low-volume power-type or aerobic sessions between hypertrophy or strength sessions may provide active recovery (AR) and/or prime performance. Finally, tapering/training cessation may be combined with priming to peak performance in training or testing. Many variables influence inter-session recovery, warranting consideration. To examine practices of coaches’ who program RT, a survey was conducted focusing on microcycle construction. Ninety-two coaches reported opinions on RT programming and non-programming factors influencing recovery and recovery monitoring methods. Coaches believed key variables influencing recovery were sleep, program design, and nutrition, and monitored self-reported sleep, muscle soreness, perceived exertion, and proximity to failure. Coaches placed high-priority sessions early in microcycles after easier lower volume, load, and proximity to failure sessions to improve recovery and performance. Coaches implemented pre-planned progression schemes while also making real-time decisions per individual recovery. These insights on practitioners’ recovery beliefs and practices highlight its importance and influence on microcycle construction, while providing application examples. With the literature and practitioners consulted, an intervention was conducted investigating the effects of four AR methods: i. four sets of one repetition (4x1) with 80% one repetition maximum (1RM) ii. 4x2x40%, iii. 20 minutes of light rowing, and iv. passive recovery (PR) control, on RT- recovery and performance measured subjectively and objectively following a muscle-damaging RT bout. Findings were reported in two publications/chapters, the first on relationships between recovery and performance, the second comparing the protocols’ effect on performance. The following recovery and performance metrics were significantly associated: (i) perceived recovery status (PRS) – squat and bench press repetitions, (ii) movement velocity at 75% 1RM (v75) – squat and bench press repetitions, and plyometric push-up (PPU), (iii) squat movement velocity against a load that elicited 1 m/s (v1) – countermovement jump (CMJ), (iv) soreness – bench press repetitions (v) heart rate variability (HRV) – PPU, and (vi) PPU – bench press repetitions. Therefore, practitioners may utilise PRS, low and high-load velocity, muscle soreness, and HRV to assess recovery and predict repetition and power performance. Comparing protocols, low-volume power-type training significantly affected subsequent low and high-load velocity. Specifically, 4x2x40% in the squat and 4x1x80% in the bench press significantly improved squat v1 and bench v75 recovery, respectively, without other significant differences between conditions. Thus, low-volume power-type AR may be programmed to enhance recovery and subsequent high-velocity, power-based performance. Future research should investigate recovery over longer periods, with different exercises, populations, and ecologically valid protocols. Mechanistic research distinguishing the impact of recovery from priming is needed. When programming RT, one should consider which variables affect recovery and use metrics that accurately assess performance. However, recovery is multifaceted, variable, and context dependent, requiring individualised approaches.